2021
DOI: 10.1080/02615479.2021.1910231
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and sleep quality among master’s students in social work

Abstract: Poor sleep quality is prevalent in professional graduate school students due to academic-and work-related stress. In addition, it has been found that high levels of perceived stress, including lifetime traumatic stress, are significantly associated with poor sleep quality. This study surveyed 196 MSW students from a university in the United States. The study revealed that the majority of MSW students had poor sleep quality, which was significantly associated with higher levels of perceived stress, poorer sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Researches have shown that the perception of stress is directly related to the individual's sleep quality, anxiety, depression and other symptoms [49][50][51]. The central symptom of depressive problems is PHQ4 "Fatigue", which means that providing some energetic activity or alleviating fatigue may help patients reducing depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Researches have shown that the perception of stress is directly related to the individual's sleep quality, anxiety, depression and other symptoms [49][50][51]. The central symptom of depressive problems is PHQ4 "Fatigue", which means that providing some energetic activity or alleviating fatigue may help patients reducing depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI) [ 12 ]; the PSQI contains 19 self-reported questions. The PSQI is the most widely used assessment tool to evaluate subjective sleep quality during the previous month, which covers a broad range of indicators relevant to sleep quality [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between stress, anxiety, depression, and poor sleep quality has been highlighted in several published studies among healthcare students [ 10 , 11 , 12 , 13 , 14 , 15 ]. A study among nursing students reported that poor sleep quality was associated with stress and symptoms of depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong evidence suggests that the cumulative effects of stress have been linked to various mental health issues, including depression [10][11][12], anxiety and suicidal ideation [13], poor sleep quality [14], challenging living conditions, health problems [15], and di culties in interpersonal relationships [16].…”
Section: Introductionmentioning
confidence: 99%